2009
DOI: 10.1007/s10895-009-0503-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-Color Two-Photon Fluorescence Laser Scanning Microscopy

Abstract: We present the first realization of a Two-Color Two-Photon Laser-Scanning Microscope (2c2pLSM) and UV fluorescence images of cells acquired with this technique. Fluorescence is induced by two-color two-photon absorption using the fundamental and the second harmonic of a Ti:Sa femtosecond laser. Simultaneous absorption of an 800 nm photon and a 400 nm photon energetically corresponds to one-photon absorption at 266 nm. This technique for Laser-Scanning Microscopy extends the excitation wavelength range of a Ti:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The main benefit of 3-PF is the excitation of molecules that absorb in the UV (e.g. the amino acid tryptophane at 266 nm), which allows label-free imaging of intrinsic protein fluorescence [168]. Other authors have used 3-PF for label-free imaging of neurotransmitters such as serotonin and dopamine, which has implications for neuronal TE [157,169].…”
Section: Three-photon-based Nonlinear Optical Microscopy Techniquesmentioning
confidence: 99%
“…The main benefit of 3-PF is the excitation of molecules that absorb in the UV (e.g. the amino acid tryptophane at 266 nm), which allows label-free imaging of intrinsic protein fluorescence [168]. Other authors have used 3-PF for label-free imaging of neurotransmitters such as serotonin and dopamine, which has implications for neuronal TE [157,169].…”
Section: Three-photon-based Nonlinear Optical Microscopy Techniquesmentioning
confidence: 99%
“…Lim and Saloma have predicted that error caused by spherical aberration is reduced with ND-2PE versus D-2PE [31]. Quentmeier et al [32,33] demonstrated UVfluorescence lifetime measurements using ND-2PE in the visible spectrum, and Robinson et al [34] demonstrated fluorescence lifetime imaging using ND-2PE combining visible and NIR wavelengths. Recently, Mahou et al demonstrated that ND-2PE can be used for simultaneous excitation of four different fluorescent proteins in mouse cerebral cortex [35].…”
Section: Introductionmentioning
confidence: 99%
“…The power of triple two-photon excitation was demonstrated to intravitally visualize three chromophores and second harmonic generation (SHG) in fly embryos 44 , and seven fluorophores in distinct cellular and tissue compartment in murine lymph nodes 38 . The triple two-photon excitation scheme is based on a wavelength mixing technique 45,46 , which implies temporal synchronization of pulse trains from two lasers with the same repetition rate as well as spatial overlap of their foci volumes (Figure 1a). The SHG can be detected from a tissue with ordered structure, i.e.…”
mentioning
confidence: 99%